CONHECIMENTOS ESCOLARES E PROFISSIONAIS PRODUZIDOS NAS INTERAÇÕES ENTRE SUJEITOS: COTRIBUIÇÕES DA EXTENSÃO - Frison, Marli D.; Boff, Eva T. d. O.; Schäffer, Francieli F.; Biasibetti, Luana; Matos, Estefani (Salão do Conhecimento, 2013)
Resumo